2016
DOI: 10.1177/0333102415618616
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL): A case report with serial electroencephalography (EEG) recordings.. Is there an association with human herpes virus type 7 (HHV-7) infection?

Abstract: Introduction The syndrome of transient headache and neurological deficits with cerebrospinal fluid lymphocytosis (HaNDL) is a diagnosis made by exclusion. In the literature, different etiological explanations are proposed for HaNDL, including an immune-mediated reaction after a viral infection. Case description We present a case of a 23-year-old woman with several episodes of transient headache, neurological deficits and cerebrospinal fluid lymphocytosis. All diagnostic criteria for the HaNDL syndrome were ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
0
21
0
4
Order By: Relevance
“…Similar findings have been described in CT studies of other stroke mimics including migraine and HaNDL (7,8). The pathophysiology of HaNDL is unknown, but it appears that cortical irritation from an atypical meningitis (9,10) may trigger a migraine-like cortical spreading depression (1,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings have been described in CT studies of other stroke mimics including migraine and HaNDL (7,8). The pathophysiology of HaNDL is unknown, but it appears that cortical irritation from an atypical meningitis (9,10) may trigger a migraine-like cortical spreading depression (1,7).…”
Section: Discussionmentioning
confidence: 99%
“…EEG is also usually performed to exclude an epileptiform origin to the presentation. Despite the scarce publication on possible EEG abnormalities in patients with HaNDL, serial EEG studies have shown that clinical symptoms of HaNDL correlate with non-specific non-epileptiform changes such as asymmetrical generalized slowing, intermittent rhythmic delta activity and triphasic waves (10). MRI might also be useful to assess a possible perfusion/diffusion mismatch (3) and, in addition, FLAIR images are able to show CSF meningeal enhancement in the sulci of the temporal and occipital lobes (14).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of HaNDL remains unclear, the major hypothesis is that the viral infection triggers the immune system dysfunction and secondarily induces transient neurological symptoms by a spreading depression-like mechanism and aseptic vasculitis.6 This hypothesis is supported by the fact that approximately 25% to 50% of patients have symptoms of viral infection or fever prior to the onset of HaNDL 2,6,15. Evidence of virus infection have been reported based on the positive serology or CSF virus detection 1618. Our patient had symptoms of upper respiratory infection.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous methylprednisolone 120mg/day was administered, since we considered that the high-dose of steroid could cease the disease course and its side effect was smaller than that of pulse therapy with intravenous methylprednisolone. Although the disease is benign and self-limited in most of the cases, HaNDL patients may have permanent visual sequela caused by elevated intracranial pressure.19 One report showed that methylprednisolone was effective for a HaNDL patient with obvious visual loss, papilloedema and ophthalmoplegia.19 Another case report showed frequent recurrence of the symptoms was relieved after intravenous administration of methylprednisolone 1,000 mg once daily for 5 days consecutively.16 We observed the rapid decrease of the intracranial pressure, and no further symptom recurrence after our patient was treated with methylprednisolone. The effectiveness of steroid supported the hypothesis that HaNDL could be due to an immune-mediated reaction after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the presence of brain waves associated with sleep (delta, theta, and alpha waves) in awake NHPs was observed. All three brain abnormalities are a sign of significant brain injury and have been observed in human cases of viral encephalitis such as Japanese encephalitis virus and Herpes simplex virus[61][62][63][64][65][66]. Further studies are underway to characterize these profound alterations in the brain waves as well as the underlying mechanism/s responsible for these abnormalities.Traumatic brain injury (TBI) is defined as a non-degenerative and noncongenital insult to the brain that results in temporary or permanent impairment of cognitive and physical functions[67].…”
mentioning
confidence: 99%